The Effect of Digital Promotion, Online Advertising, and Customer Service Quality on the Decrease in Tokopedia Purchases Amid Competitive E-Commerce Competition in Mataram City - Putri Dewi Santika; Handry Sudiartha Athar (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aimed to investigate the impact of digital promotion, online advertising, and customer service quality on changes in consumer purchasing behavior on the Tokopedia platform amid the growing competition within the e-commerce industry in Mataram City. The research employed a quantitative method using a survey design. A total of 100 respondents were selected through purposive sampling based on predetermined criteria, with the study focusing on active Tokopedia users who had experience conducting transactions on the platform. Data obtained from the questionnaires were processed and analyzed using multiple linear regression analysis with the support of SPSS version 27 software. The findings revealed that digital promotion, online advertising, and customer service quality significantly influenced the decrease in purchasing activity on Tokopedia. Both the partial and simultaneous tests confirmed that these variables contributed significantly to explaining variations in consumer purchasing behavior. In addition, digital promotional efforts and online advertising were shown to influence consumers’ purchasing intentions, while customer service quality emerged as an important factor in maintaining customer loyalty and continued platform engagement.